2016
DOI: 10.1080/1067828x.2016.1175985
|View full text |Cite
|
Sign up to set email alerts
|

Hookah Use: Could Families Be A Risk Factor for Future Addiction?

Abstract: Research indicates that smoking a hookah has health and addiction risks. In substance abuse research the family is often a protective factor in reducing youth substance use. However, this may not be the case for smoking a hookah. The aim of the current study was to examine the use of the hookah in the family. This was a cross-sectional descriptive study of 837 South African adult participants, 51.7% males and 48.3% females. The mean age of participants was 35.29 (SD D 15.11) years. The results indicate that fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…(4) Including younger children: It would be beneficial for younger children to have adequate knowledge about hookah pipe smoking and have the skills to decline when offered to experiment as studies have found children younger than 10 years old using the hookah pipe (Roman et al, 2017). However, it may not be suitable to include children younger than 10 years old in this particular intervention as their developmental levels are different to that of an adolescent.…”
Section: Discussionmentioning
confidence: 99%
“…(4) Including younger children: It would be beneficial for younger children to have adequate knowledge about hookah pipe smoking and have the skills to decline when offered to experiment as studies have found children younger than 10 years old using the hookah pipe (Roman et al, 2017). However, it may not be suitable to include children younger than 10 years old in this particular intervention as their developmental levels are different to that of an adolescent.…”
Section: Discussionmentioning
confidence: 99%
“…[18,[27][28][29] Research shows there is a link between peer pressure, social acceptance and smoking cigarettes, but this is unknown for the hookah pipe. [30] Therefore, this study sought to compare the relationship between peer pressure and social acceptability among hookah pipe users and non-users.…”
Section: Research Articlementioning
confidence: 99%
“…The World Health Organization has emphasized on the identification of WTS gender-specific contributing factors (WHO, 2010 ); nonetheless, little efforts have been made so far in this area. A handful of studies in this area reported that WTS contributing factors include personal factors such as curiosity, positive attitude towards WTS, and personal pleasure, as well as interpersonal and environmental factors such as lack of emotional family support, WTS by family members, peer pressure, lack of healthy recreational activities, inexpensiveness and easy accessibility of WTS, and lack of public educations against WTS (Akl et al, 2015 ; Gathuru et al, 2015 ; Jawad et al, 2015 ; Mao et al, 2014 ; Nakkash et al, 2011 ; Ramji et al, 2015 ; Roman et al, 2017 ; Villanti et al, 2015 ). The results of studies on women’s perceptions of WTS were different from the results of studies on men.…”
Section: Introductionmentioning
confidence: 99%